(untitled) (Journal of the College of Education for Women, 2019)
The Social life contain an important side from the inherited Civilization to anynation, is distinguished by activity and zeal. The old Indian is characterized withclosed and solidify socilal systems. This state had its influences on the activities of thesocial movment. It astonished the conquered mushins – Arab to the India from the endof the first centuny A.H we tried to change it by good works and made them becomeaware, so this made radical active in the social India in Islamic period which is formhumanbeing nobilitie and their active deal in the society.